"I Am Aware, but Who Am I to Comment.": Critical Stance in Indonesian EFL Students' Academic Essay (NOBEL: Journal of Literature and Language Teaching, 2022)
The study examined the reporting verbs (RV) and tenses of RV in the academic essay of English-majored undergraduate students in Indonesia. Employing a sequential explanatory mixed-method research design, the study first collected quantitative data in the form of frequency of RV using Hyland’s (2002) framework and tenses of RV using Thomas and Hawes’ (1997) framework. Qualitative data were then collected to explain the reasons behind the use of RV and the tenses of RV. The study found that discourse verbs are prevalent in the students’ essays, with 66,67% occurrence of total corpus, followed by research verbs, with 30,72% occurrence of the total corpus. Cognition verbs, however, were the least used, with 2,61% of the total corpus. The study also found that present tense (58,82%) and past tense (41,18%) were the most frequently used tenses in students’ RV. The interview revealed students’ reasons behind the frequent use of discourse and research verbs and the limited use of cognition verbs in their essays. Among which are their lack of engagement with literature and reticence to evaluate the author’s claims due to their inadequate cognitive competence and English proficiency. The study concludes that students’ use of discourse and research verbs reflects their relatively low criticality toward the cited materials.